Finding the center within : - Bien, Thomas (John Wiley & Sons, 2003)
Finding the Center Within offers a step-by-step program for breaking down the barriers that prevent us from actualizing our wise inner self. The Biens combine Eastern spiritual wisdom with the pragmatic wisdom of Western psychology, teaching us how to remove the walls that conceal who and what we really are and face our lives with greater honesty.